English Language Training for Village Communities Affected by Yogyakarta International Airport Development - Kusumaningrum, Maria Asumpta Deny; Rahmawati, Fajar Khanif; Kumolosari, Eli (Joong-Ki : Jurnal Pengabdian Masyarakat, 2024)
It is hoped that the construction of the airport will have a real impact on the economy in the tourism, hotel, service industry and trade sectors for the surrounding community. The existence of the airport has an economic and social impact on the affected village which is the object of the training, namely Glagah Village in Temon District, Kulon Progo. To develop the economy, it is not only related to facilities and infrastructure, but also needs to be supported by human resources, one of whom is able to communicate using English. The English language skills of the village community around the airport are classified as being able to communicate but are still lacking based on the results of the pre-test given. There are still difficulties faced both in terms of listening English speech, understanding English reading, composing English sentences, and expressing ideas in speaking English. Thus, English language training is still needed to improve their quality. This community service activity is carried out in the form of training in the form of theoretical and practical exposure. The method used is Communicative Language Teaching (CLT). The activity took place 5 meetings with activity stages including warming up, core activities (speaking, writing, reading, and listening) and evaluation. Overall, it can be said that the activity was carried out well. It can be seen from the evaluation results distributed to training participants. All of them received a good response from the training participants. The participants' English language skills also increased based on the test results given to the participants.